2016
DOI: 10.1097/01.ewx.0000471573.70688.60
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum interleukin-12 and interferon-γ in patients with multiple warts treated with intralesional tuberculin injection

Abstract: BackgroundPrevious studies have shown favorable results for immunotherapies in the treatment of warts. However, the exact mechanism of action of injectable antigens is still unclear. It has been proposed that injectable antigens elicit a cell-mediated hypersensitivity reaction leading to T-helper 1 (Th1) activation with cytokine release. Objective To evaluate the levels of Th1 cytokines -interleukin-12 (IL-12) and interferon-g (IFN-g) -in responders and nonresponders to immunotherapy using 'protein purified de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…These results were in agreement with those of El‐Samahy et al who have reported that serum levels of IL‐12 and IFN‐γ were not increased after treatment with PPD in both responders and non‐responders.…”
Section: Discussionsupporting
confidence: 93%
“…These results were in agreement with those of El‐Samahy et al who have reported that serum levels of IL‐12 and IFN‐γ were not increased after treatment with PPD in both responders and non‐responders.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 54 studies of 3,446 enrolled patients was deemed finally eligible [Table 2]. Overall, 13 studies with 747 patients in the MMR group [10][11][12][13][14][15][16][17][18][19][20][21][22] ; 12 studies with 436 patients in the Candida group [23][24][25][26][27][28][29][30][31][32][33][34] ; nine studies with 311 patients in the Vitamin D group 25,[35][36][37][38][39][40][41][42] ; six studies with 235 patients in the PPD group 38,[43][44][45][46][47] ; six studies with 197 patients in the interferon-α group [48][49][50][51][52][53] ; four studies with 127 patients in the Mw group [54]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The overall complete response rate was 60.6% (95% confidence interval: 54.8-66.5%) among 53 studies with 2,548 patients [Figure 2a]. The complete response ratio of the Mw group was 73.1% (95% confidence interval: 55.6-90.6%) in four studies, [54][55][56][57]63 the Candida group was 62.6% (95% confidence interval: 53.3-71.9%) in 11 studies, 23,24,[26][27][28][29][30][31][32][33][34] MMR group was 63.2% (95% confidence interval: 53.1-73.4%) in 13 studies, [10][11][12][13][14][15][16][17][18][19][20][21][22] PPD group was 62.7% (95% confidence interval: 42.4-83.0%) in six studies, 38,[43][44][45][46][47] Vitamin D group was 54.2% (95% confidence interval: 32.7-76.0%) in eight studies, [35][36][37][38][39][40][41][42] interferon-α group was 51.9% (95% confidence interval: 27.0-76.9%) in six studies, [48]…”
Section: Treatment Response Of Injected and Nearby Lesionsmentioning
confidence: 99%
“…In the present study, intralesional injection of PPD was associated with complete clearance of all warts in 81.7% of patients. This was higher than the resolution rates reported by Moubasher et al 7 (73.9%), Saoji et al 8 (76%), Amirnia et al 9 (77.1%), Ahmed et al 10 (66.6%) Nimbalkar et al 11 (62.2%), and El‐Samahy et al 12 (56%). All of them included both adults and children.…”
Section: Discussionmentioning
confidence: 58%